Shedding light on the entropy change found for the transition stage II→stage I of Li-ion storage in graphite - Leiva, Ezequiel Pedro Marcos; Perassi, Eduardo Marcelo; Barraco Díaz, Daniel Eugenio (2024)
Fil: Leiva, Ezequiel Pedro Marcos. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas; Argentina.